2019
DOI: 10.1002/ca.23438
|View full text |Cite
|
Sign up to set email alerts
|

Spinal dural sac termination and internal filum terminale fusion

Abstract: Surgery for tethered spinal cord caused by thickened filum terminale (FT) is frequently performed through S1 laminectomy based on the assumption that the internal FT (FTi) fuses with dura mater at S2 vertebral level. Literature on specific study for the site of its fusion and dural sac (DS) termination was rather limited. Moreover, there is no large anatomical study in Asian population. To determine the anatomy, examination of the FTi fusion site, as well as the region at which DS ended, was undertaken. From 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The terminal portion of the sac was cone‐shaped, and its narrowing, as a rule, begins at the level of L5 and S1 vertebrae. Numerous other studies using imaging (Soleiman et al, 2005) or cadavers have also confirmed that the termination of dura occurs at S2 in >80% of cases (Pokanan, Borsu, & Hansasuta, 2019). Moreover, termination levels do not vary with subject sex, but they do so with subject age (Soleiman et al, 2005).…”
Section: Discussionmentioning
confidence: 78%
“…The terminal portion of the sac was cone‐shaped, and its narrowing, as a rule, begins at the level of L5 and S1 vertebrae. Numerous other studies using imaging (Soleiman et al, 2005) or cadavers have also confirmed that the termination of dura occurs at S2 in >80% of cases (Pokanan, Borsu, & Hansasuta, 2019). Moreover, termination levels do not vary with subject sex, but they do so with subject age (Soleiman et al, 2005).…”
Section: Discussionmentioning
confidence: 78%
“…Several studies have determined the termination level of DS in adults by conducting cadaveric and MRI-based studies in different populations [ 4 , 5 , 8 , 15 ]. We conducted a cross-sectional MRI-based study in the previously unstudied Saudi population to observe and document the termination level of the DS.…”
Section: Discussionmentioning
confidence: 99%
“…Practitioners were previously relying on cadaveric assessment. However, it was discovered to be limited clinical benefit [ 4 , 5 ]. Other forms of practice included an invasive procedure known as myelography.…”
Section: Introductionmentioning
confidence: 99%